Troponin least significant change (z-score) is associated with poor clinical outcomes in patients presenting to the emergency department. (July 2021) - Smith, Joel D; Leong, Kai'En; Fazio, Timothy; Chiang, Cherie
Background: A rise and/or fall in high sensitivity cardiac troponin (hs-Tn) is critical in defining acute myocardial injury and therefore the diagnosis of acute myocardial infarction. A significant rise in hs-Tn is not well defined in current guidelines. Calculation of a z-score for two consecutive hs-Tn measurements is a method-independent measure of dynamic troponin elevation. However, the association of hs-Tn z-score with outcomes for unselected emergency department admissions is unknown. Moreover, the association of non-dynamic troponin elevations, as defined by a normal z-score, with clinical outcomes remains to be assessed. Methods: We retrospectively calculated z-scores for patients presenting to emergency department over 18 months who had serial troponin measurements with at least one result >99th percentile using the Abbott hs-TnI assay. We assessed the association of z-score with discharge diagnosis, cardiac interventions, inpatient mortality, length of stay and readmission rates. Results: There were 2062 presentations for 1830 patients where a z-score was calculated. Z-score was elevated in 1080 presentations. Dynamic troponin elevation (z-score ≥ 2) was associated with acute myocardial infarction (OR = 9.1, P  < 0.01), admission to an inpatient unit (95 vs. 88%, P  < 0.01), increased inpatient length of stay (97 vs. 65 days, P  < 0.01), inpatient coronary intervention (21 vs. 6%, P  < 0.01) and mortality (4.4 vs. 2.4%, P  < 0.05) compared with myocardial injury with a static troponin elevation. Conclusions: Z-score is an assay-independent tool to alert clinicians of significant, dynamic troponin elevation and acute myocardial injury. It is associated with poorer clinical outcomes.